2010
DOI: 10.1186/1756-9966-29-136
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A expression is increased in prostate cancer

Abstract: BackgroundThe CIP2A protein is a recently characterized oncoprotein which inhibits protein phosphatase 2A activity. Expression of CIP2A has been detected in several carcinomas, but its expression and significance in prostate cancer has not been examined so far.MethodsExpression of the CIP2A protein was studied using immunohistochemistry in prostate cancer (n = 59) and in benign prostatic hyperplasia (n = 20) specimens. The CIP2A staining scores were compared with several clinicopathological parameters.ResultsE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 11 publications
2
54
0
1
Order By: Relevance
“…Moreover, CIP2A expression predicts poor patient prognosis in certain gastric cancer subtypes and in non-small cell lung cancer (Khanna et al, 2009;Dong et al, 2010). In breast cancer, CIP2A expression correlates with disease aggressiveness and in prostate cancer with a high Gleason's score (Come et al, 2009;Vaarala et al, 2010). Taken together, these studies have firmly established CIP2A as a novel, clinically relevant human oncoprotein.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, CIP2A expression predicts poor patient prognosis in certain gastric cancer subtypes and in non-small cell lung cancer (Khanna et al, 2009;Dong et al, 2010). In breast cancer, CIP2A expression correlates with disease aggressiveness and in prostate cancer with a high Gleason's score (Come et al, 2009;Vaarala et al, 2010). Taken together, these studies have firmly established CIP2A as a novel, clinically relevant human oncoprotein.…”
Section: Introductionmentioning
confidence: 59%
“…CIP2A depletion results in inhibition of malignant cell growth and inhibition of tumor growth in mouse xenograft models (Junttila et al, 2007;Come et al, 2009). CIP2A is overexpressed in most major solid human cancer types, including head and neck squamous cell carcinomas as well as gastric, esophageal, breast, colon, lung and prostate cancer (Junttila et al, 2007;Li et al, 2008;Come et al, 2009;Khanna et al, 2009;Dong et al, 2010;Katz et al, 2010;Qu et al, 2010;Vaarala et al, 2010). Strikingly, with the exception of breast cancer, in which 40% of patient samples overexpress CIP2A (Come et al, 2009), all other studied human cancer types have CIP2A overexpression in 65-90% of patient samples.…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition to HCC, CIP2A is over-expressed in several human malignancies including gastric cancer, head and neck cancer, colon cancer, breast cancer, prostate cancer and non-small cell lung cancer. [19][20][21][22][23][24][25] Similarly, Come et al 25 found that CIP2A is associated with clinical aggressiveness in human breast cancer and promotes the malignant growth of breast cancer cells. Of note, very recently CIP2A has been found to be related to hematologic malignancies; in the first case recorded, an MLL-KIAA1524 fusion gene was identified in an infant with acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%
“…Cancerous inhibitor of PP2A (CIP2A), which is known to enhance the migration and proliferation of tumor cells, is overexpressed in various types of human cancers, including breast (Come et al 2009, Niemela et al 2012, Tseng et al 2012, Laine et al 2013, prostate (Vaarala et al 2010), lung (Dong et al 2011), pancreatic (Wang et al 2013), bladder (Huang et al 2012a), blood or bone marrow (Lucas et al 2011, colon (Teng et al 2012), ovarian (Bockelman et al 2011b), cervical (Huang et al 2010), tongue (Bockelman et al 2011a), oral (Basile & Czerninski 2010), esophageal squamous (Qu et al 2012), and head and neck squamous (Ferreira et al 2004) cancers. CIP2A expression is transcriptionally enhanced by Ets1 (Zhao et al 2010), and the concurrent binding of Ets1 and Elk1 to the proximal CIP2A promoter is absolutely required for CIP2A expression in cervical, endometrial, and liver carcinoma cell lines (Huang et al 2012b, Pallai et al 2012.…”
Section: Introductionmentioning
confidence: 99%